Supporting long‐term sustainability of ex situ collections using a pedigree‐based population management approach - Foster, Jeremy A.; Walsh, Seana K.; Havens, Kayri; Kramer, Andrea T.; Fant, Jeremie B. (Applications in plant sciences, 2022)
Premise Living collections maintained for generations are at risk of diversity loss, inbreeding, and adaptation to cultivation. To address these concerns, the zoo community uses pedigrees to track individuals and implement crosses that maximize founder contributions and minimize inbreeding. Using a pedigree management approach, we demonstrate how conducting strategic crosses can minimize genetic issues that have arisen under current practices. Methods We performed crosses between collections and compared progeny fitness, including plant performance and reproductive health. We genotyped the progeny and parental accessions to measure changes in diversity and relatedness within and between accessions. Results The mean relatedness values among individuals within each accession suggest they are full siblings, demonstrating that there was high inbreeding and low diversity within accessions, although less so among accessions. Progeny from the wider crosses had increased genetic diversity and were larger and more fertile, while self‐pollinated accessions were smaller and less fertile. Discussion Institutions that hold exceptional species should consider how diversity is maintained within their collections. Implementing a pedigree‐based approach to managing plant reproduction ex situ will slow the inevitable loss of genetic diversity and, in turn, result in healthier collections.